Femoral Neck Fracture in Geriatri Patient: A Case Studies and Approaches to Post-Operative Rehabilitation: A Literature Review - Winata, Lionesya Sukma; Prawiragara, Fachrizal Arfani (Faculty of Medical - UPN Veteran Jawa Timur, 2025)
Introduction: Femoral collum fractures are a common injury in the geriatric population, particularly postmenopausal women with osteoporosis. The intracapsular location of the fracture and proximity to the blood supply of the femoral head increases the risk of complications such as non-union and avascular necrosis. Early and appropriate treatment is essential to minimize long-term functional impact. Case Illustration: A 67-year-old woman experienced severe pain in the right hip after slipping while mopping the floor. The patient was unable to stand or walk after the incident. History showed osteoporosis which was not treated regularly. Radiologic examination revealed a right collum femur fracture with Garden type IV classification. The patient underwent arthroplasty bipolar and a gradual physiotherapy rehabilitation program for six months. Discussion: This case illustrates a common pattern of osteoporotic fractures in the elderly, where minor trauma can cause severe damage to the bone. The selection of arthroplasty is appropriate to the patient's bone condition and fracture type, providing stability and allowing early mobilization. Intensive rehabilitation has been shown to support functional recovery. Long-term management of osteoporosis with antiresorptive therapy such as zoledronate, patient education, and environmental modification are also important for the prevention of recurrent fractures. Conclusion: A comprehensive approach that includes surgery, early rehabilitation, and management of osteoporosis can result in a better.